Women and the Texas Revolution - Scheer, Mary L., 1949- (Practical guide series (Denton, Tex.) ;, 2012)
While there is wide scholarship on the Texas Revolution, there is no comparable volume on the role of women during that conflict. Most of the many works on the Texas Revolution include women briefly in the narrative, such as Emily Austin, Suzanna Dickinson, and Emily Morgan West (the Yellow Rose), but not as principal participants. Women and the Texas Revolution explores these women in much more depth, in addition to covering the women and children who fled Santa Anna's troops in the Runaway Scrape, and examining the roles and issues facing Native American, Black, and Hispanic women of the tim.